Vesta surface thermal properties map. Issue 5 (7th March 2014) - Capria, M. T.; Tosi, F.; De Sanctis, M. C.; Capaccioni, F.; Ammannito, E.; Frigeri, A.; Zambon, F.; Fonte, S.; Palomba, E.; Turrini, D.; Titus, T. N.; Schröder, S. E.; et al.
Abstract The first ever regional thermal properties map of Vesta has been derived from the temperatures retrieved by infrared data by the mission Dawn. The low average value of thermal inertia, 30 ± 10 J m−2 s−0.5 K−1, indicates a surface covered by a fine regolith. A range of thermal inertia values suggesting terrains with different physical properties has been determined. The lower thermal inertia of the regions north of the equator suggests that they are covered by an older, more processed surface. A few specific areas have higher than average thermal inertia values, indicative of a more compact material. The highest thermal inertia value has been determined on the Marcia crater, known for its pitted terrain and the presence of hydroxyl in the ejecta. Our results suggest that this type of terrain can be the result of soil compaction following the degassing of a local subsurface reservoir of volatiles.